Distributed CMOS bidirectional Amplifiers : broadbanding and linearization techniques - El-Khatib, Ziad (Analog Circuits and Signal Processing, 2012)
This book describes methods to design distributed amplifiers useful for performing circuit functions such as duplexing, paraphrase amplification, phase shifting power splitting and power combiner applications.  A CMOS bidirectional distributed amplifier is presented that combines for the first time device-level with circuit-level linearization, suppressing the third-order intermodulation distortion. It is implemented in 0.13μm RF CMOS technology for use in highly linear, low-cost UWB Radio-over-Fiber communication systems. Describes CMOS distributed amplifiers for optoelectronic applications such as Radio-over-Fiber systems, base station transceivers and picocells; Presents most recent techniques for linearization of CMOS distributed amplifiers; Includes coverage of CMOS I-V transconductors, as well as CMOS on-chip inductor integration and modeling; Includes circuit applications for UWB Radio-over-Fiber networks.